2008
DOI: 10.1117/12.760516
|View full text |Cite
|
Sign up to set email alerts
|

Using NIR spatial illumination for detection and mapping chromophore changes during cerebral edema

Abstract: We used spatially-modulated near-infrared (NIR) light to detect and map chromophore changes during cerebral edema in the rat neocortex. Cerebral edema was induced by intraperitoneal injections of free water (35% of body weight). Intracranial pressure (ICP) was measured with an optical fiber based Fabry-Perot interferometer sensor inserted into the parenchyma of the right frontal lobe during water administration. Increase in ICP from a baseline value of 10 cm-water to 145 cm-water was observed. Following induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…As stated above, this behavior demonstrates the morphologic changes that occurred in the brain during CHI and highlights the presence of cellular swelling within brain parenchyma. 10,43,[56][57][58] For completeness of scattering processing, we next present qualitative image maps of both A and sp. At this point, we have a spectral cube with dimensions of 200 × 200 × 6, where 200 × 200 is the 2-D image pixel size and 6 stands for the number of the wavelengths used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As stated above, this behavior demonstrates the morphologic changes that occurred in the brain during CHI and highlights the presence of cellular swelling within brain parenchyma. 10,43,[56][57][58] For completeness of scattering processing, we next present qualitative image maps of both A and sp. At this point, we have a spectral cube with dimensions of 200 × 200 × 6, where 200 × 200 is the 2-D image pixel size and 6 stands for the number of the wavelengths used.…”
Section: Discussionmentioning
confidence: 99%
“…28 As will be detailed in Secs. 2.3 to 2.5, the present study differs from previous reported structured illumination methods [9][10][11][12][13][14]27,28 in the simplicity in the way the optical properties were obtained (using high-and low-spatial frequencies) and in the calibration procedure. Out of these, for the reader's knowledge, the use of sinusoidal pattern is also popular as a super-resolution platform, 29 in machine vision, 30 and in the area of optical image processing, specifically when three-dimensional (3-D) object surfaces measuring (profilometery) is on-demand.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…35 Over recent decades, several studies have described the instrumentation of spatially modulated illumination and its use in noncontact and scan-free imaging in a variety of biomedical applications [36][37][38][39][40][41][42] and in the clinic. 43 Spatially modulated illumination is a multispectral wide-field imaging modality that utilizes NIR periodic illumination patterns with sinusoidal frequencies of up to 0.5 mm −1 to separately derive and spatially map the absolute values of the optical properties of tissue, i.e., absorption (μ a ) and reduced light scattering (μ 0 s ) coefficients of turbid media.…”
Section: Spatially Modulated Illuminationmentioning
confidence: 99%
“…Optimization of the frequency parameter was reported by Bodenschatz [6] and Hu [12] for spatial frequency imaging of biological materials. The widespread use of spatial modulation for mapping turbid media in different optical techniques, with its potential applications in human disease (ischemic stroke [10], Alzheimer's disease [11] and cerebral edema [13], etc. ), led us to examine the modulation effect on our method.…”
Section: Introductionmentioning
confidence: 99%